Barriers to care for patients with diabetes in Durham, North Carolina, why are we withholding life-sustaining medications from the patients who need them the most?. Issue 5 (September 2015) - Spratt, Susan E; Feinglos, Mark N; Willis, Janese M
<x xml:space="preserve">Abstract</x> The diabetes epidemic and its complications disproportionately affect minorities and the poor. Medical treatments that can prevent or delay diabetes complications are widely available but poverty underlies much of why there are disparities in diabetes care and outcomes. Lack of access to care, food insecurity and inability to pay for medications prevents adherence to a medication and lifestyle regimen that can be life-sustaining. At the very least, US policies should be changed to provide life-sustaining medications that prevent costly complications to patients who cannot afford them. Adopting value-based insurance design would benefit patients with diabetes who cannot afford to pay for medications but would also reduce healthcare costs in the long run.